Emprego público e desigualdade de renda: um estudo de causalidade para os municípios brasileiros - França, Vitor Augusto Meira (2008)
This paper analyzes the relation between public employment and income inequality for Brazilian municipalities. In particular, a theoretical model is developed to demonstrate that public employment can be used to concentrate income. Next, using the Fiscal Responsibility Law as exogenous instrument for public employment, an empirical test is provided to test that hypothesis. The results suggest that public employment concentrates income instead of redistribute. The estimations are larger than if one ignores the simultaneous bias and estimate the model directly through standard technique. It is not claimed that public employment is used explicitly by the local governments to concentrate income; however, the estimations suggest that is the consequence of its operation.